The influence of emotional intelligence on, political behaviour of students - Johar, Siti Sarawati; Sanif, Sazuliana; Ani, Fauziah; Md. Yusoff, Rosman (Future Academy, 2018)
This paper discusses the importance of strengthening emotional intelligence (EI) among youths to achieve more integrated human domains. Human capital resources targeting youths are one of the main thrusts of national development in Malaysia especially from the political, economic, social and educational aspects. The main purpose of this study was to test the presence of and the significance (if any) of the relationship between EI competence and the constructs determining youths’ political behaviour. A total of 313 students from four public universities in Malaysia were selected as the sample. The Emotional Intelligence Self-Description Inventory (EISDI), and Political Behaviour Questionnaire (PBQ) were used to obtain data which was analysed using correlation and regression analysis. The findings showed that the two hypotheses were accepted, i.e. there is a correlation between EI with political behaviour which significantly influenced EI on the constructs of political behaviour namely conservativism and nationalism. Hence, EI can be construed to be a determining factor in behaviour and ideology that signifies political maturity among Malaysian youth